Lembaga Arisan Online dalam Perspektif Hubungan Hukum Perjanjian - Era Fasira; Ali Imron (Postgraduate University of Merdeka Malang, 2022)
The purpose of this research is to analyze the Arisan Online Institution in the Perspective of Agreement (Contract) Legal Relations. The existence of arisan institutions is a form of kinship relationship among local communities based on the principle of helping each other, mutual cooperation. Its existence from the past until now seems to want to say a million benefits. It is now not just a place to save money. When viewed from the contractual relationship, it is a form of association regulated in Article 1653 of the Civil Code. There is a legal relationship between participants and managers in an arisan that is mutually agreed upon. The arisan relationship arises because of the agreement. From the agreement, rights and obligations arise. Participants have obligations that must be fulfilled, namely paying a sum of money according to the amount of arisan, while the manager is obliged to pay to participants if participants get arisan motels. The legal relationship between the collection of arisan arisan funds is that each independent collects a certain amount of funds, which will then be paid to each member in turn in the same value based on the agreement that has been made. This legal relationship is analogous to mutual insurance as stipulated in Article 286 of the KUHDDOI: https://doi.org/10.26905/mlj.v3i1.7928